양화사 구문의 조응어 해석 - 정소우(Chung So-Woo) (영어학, 2009)
This paper proposes a left‐to‐right analysis of anaphora in quantificational structures in terms of Discourse Representation Theory. The principles of anaphoric resolution do not resort to any particular syntactic theory and are defined solely in terms of lexical information and accessibility between discourse representation structures and discourse referents. Every element is processed in the order of occurrence and quantifiers in a non-sentence-initial position cause the ongoing DR to split in two with the same index, in two different fashions depending on its scope with respect to other operators. DRS conditions and accessibility are accordingly modified so that DRs introduced by sentence-initial quantifiers can be accessible from DRs introduced by quantifiers in other position no matter what their relationships are. KCI Citation Count: 1